1993
DOI: 10.1007/bf02125430
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic study of paternity after cryptorchidism: Initial results

Abstract: Paternity has been studied among married men who were formerly cryptorchid. Forty-one of 52 formerly unilateral cryptorchid men were married, 10 of 11 bilaterally cryptorchid and 36 of 42 control men. Thirty-two of the 41 of the unilateral group (78%) had fathered children, 6 of 10 in the bilateral group (60%) and 24 of 36 controls (67%). These limited data from the initial phase of this study of paternity after cryptorchidism do not show any correlation between paternity or time of unprotected intercourse to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…This controlled study of paternity after cryptorchidism expands upon the initial preliminary report of our current project [9] which defines paternity to include not only all married men, but also those men who have fathered children or attempted paternity. All but one previous study [4] reported paternity among married men, without considering those who had tried to verify their capability of paternity.…”
Section: Discussionmentioning
confidence: 85%
“…This controlled study of paternity after cryptorchidism expands upon the initial preliminary report of our current project [9] which defines paternity to include not only all married men, but also those men who have fathered children or attempted paternity. All but one previous study [4] reported paternity among married men, without considering those who had tried to verify their capability of paternity.…”
Section: Discussionmentioning
confidence: 85%
“…En effet, Lee et al [12] ont montré que lorsque l'abaissement testiculaire est effectué avant l'âge de 15 ans, la cryptorchidie unilatérale n'altère que légèrement la paternité à l'âge adulte. Ils ont aussi établi qu'il n'y aurait pas en ce moment de corrélation entre la paternité à l'âge adulte et l'âge du patient au moment de l'abaissement testiculaire [13].…”
Section: Discussionunclassified
“…The data concerning the effects of cryptorchidism on subsequent fertility reveal discrepancies in the literature [8]. Reduced spermatogenesis and infertility, as a result of cryptorchidism, has often been described [9,10], while other authors have refused this association [11,12].…”
Section: Introductionmentioning
confidence: 56%